The Aesthetics of Artistic Imagery in the Wisdom of Imam Ali (peace be upon him) in Nahj al-Balagha - Maitham Razzaq Jabbar al-Zurfi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Artistic imagery is a central element of rhetoric that translates abstract thought into perceptible expression within Arabic literary tradition. Specific Background: In Nahj al-Balagha, the wisdom of Imam Ali (peace be upon him) presents a distinctive rhetorical model grounded in figurative and sensory representation. Knowledge Gap: Despite previous rhetorical studies, limited research has examined the aesthetic structure and integrated functions of artistic imagery in his aphoristic rulings through a focused descriptive-analytical approach. Aims: This study analyzes the composition, types, and aesthetic, semantic, and persuasive roles of artistic imagery in Imam Ali’s wisdom. Results: The analysis shows that simile, metaphor, metonymy, allegory, and sensory, mental, and kinetic imagery embody moral and philosophical meanings in concrete forms, creating a unified expressive system that combines beauty, intellectual depth, and value-oriented guidance. Novelty: The study demonstrates that artistic imagery constitutes the structural core of Imam Ali’s rhetoric through an organic unity between form and ethical content. Implications: The findings position Nahj al-Balagha as a complex literary and rhetorical model for aesthetic and critical studies in Arabic and Islamic literature. Highlights • Identifies sensory and cognitive figurations as structural components of aphoristic discourse.• Demonstrates integration of moral philosophy with figurative composition.• Establishes proverbial sayings as a comprehensive rhetorical system. Keywords Artistic Imagery; Rhetorical Aesthetics; Nahj Al-Balagha; Imam Ali; Arabic Literature